2022
DOI: 10.2337/ds21-0093
|View full text |Cite
|
Sign up to set email alerts
|

Improved Time in Range During 28 Days of Meal Delivery for People With Type 2 Diabetes

Abstract: Objective Nutrition therapy is a cornerstone of care for people with type 2 diabetes, yet starting new, healthy eating behaviors and sustaining them can be challenging. This decentralized, single-arm study assessed the impact of 28 days of home-delivered, pre-portioned meals (three meals per day) on continuous glucose monitoring (CGM)-derived glycemic control and quality of life. Research design and methods We enrolled 154 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…If hypoglycemia alternates with hyperglycemia, an individual’s HbA 1c may not rise to a level that is considered poorly controlled. At least one study has demonstrated improvement in continuous glucose monitor (CGM) time in range during meal delivery for individuals with T2D, 48 and CGM has demonstrated an ability to differentiate individuals who have T2D or who are at risk or pre-DM in a predominantly Hispanic sample. 49 Thus, assessment of glycemic variability using CGM may be a better metric of control in future studies, although not available in national survey data.…”
Section: Discussionmentioning
confidence: 99%
“…If hypoglycemia alternates with hyperglycemia, an individual’s HbA 1c may not rise to a level that is considered poorly controlled. At least one study has demonstrated improvement in continuous glucose monitor (CGM) time in range during meal delivery for individuals with T2D, 48 and CGM has demonstrated an ability to differentiate individuals who have T2D or who are at risk or pre-DM in a predominantly Hispanic sample. 49 Thus, assessment of glycemic variability using CGM may be a better metric of control in future studies, although not available in national survey data.…”
Section: Discussionmentioning
confidence: 99%